Pembelajaran Komunikasi Politik Menyambut Pemilihan Umum Serentak di Indonesia - Ida Ayu Made Yuni Andari; Ida Bagus Alit Arta Wiguna (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Political communications include forms of communication that occur in the political environment, including communications in elections, political campaigns, policy making, political decision making, and interactions between government and society. This research aims to analyse how democratic communication ahead of the general election, to study the communication of political elites and parties, the communication of parties participating in the 2024 general election with the community, the involvement of religious leaders in political communication, internal party and inter-party communication. In this research, the author uses a qualitative research method with a content analysis approach. Data processing in this research is done by critical analysis, comparison, and interpretation of various search results from primary and secondary sources. The results of this research are 1) A deep understanding of the target audience that is relevant and attractive to voters 2). Utilisation of social media and digital technology 3). Transparency and trust are key in building a good relationship between political parties, candidates, and voters 4). Accurate and objective voter education about the electoral process 5). Collaboration with voters 6). Responsiveness to emerging issues is important in maintaining relevance and speed in delivering political messages. 7). Evaluation of the communication strategy used.